Population dynamics of aphid species in Korean seed potato cultivation area over four decades. Issue 4 (20th February 2019) - Kim, Juil; Kwon, Min
Abstract: The world's climate is changing. This can affect agricultural insects and the damage they cause by altering their ecology, behavior and habitats. Aphids are emerging as an indicator of climate change, and they are a good model for understanding these environmental changes, especially based on their migratory behavior. In this study, the occurrence of aphids in a seed potato field in Pyeongchang, Korea, was monitored daily using a yellow water pan trap from 1977 to 2017. During these 40 years, the annual migration fluctuations of the aphids were analyzed, with particular focus on four species known to vector potato viruses, Aphis gossypii, Aulacorthum solani, Macrosiphum euphorbiae, and Myzus persicae . It was found that, as time goes by, the start point of spring migration in these aphid species was getting earlier while the peak in autumn migration gradually moved to the winter season. Moreover, the annual total number of collected aphids increased by 3.74 times during the 40 years. Together with a mean annual temperature increase of 1.03°C in Pyeongchang over the past four decades, there is a potential threat of expansion in the distribution of aphid species. Therefore, we carefully hypothesized that this temperature change could influence the aphid's population changes in the Korean peninsula. This information can be used in an integrated aphid management program in seed potato cultivation.